Pemanfaatan Teknologi Cloud Terhadap Aktivitas Desa Cibening Melalui UMKM Berbasis Digital Entrepreneur - Akmaludin, Akmaludin; Sihombing, Erene Gernaria; Rinawati, Rinawati; Ariswati, Ester (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2023)
UTILIZATION OF CLOUD TECHNOLOGY IN VILLAGE ACTIVITIES THROUGH DIGITAL ENTREPRENEUR-BASED MSMES. Cibening is one of the villages in Setu District, Bekasi Regency, West Java Province. Residents of Cibening Village certainly want to know and be introduced to use of Cloud technology for PKK mothers and Cibening Village Staff through digital entrepreneurship-based MSMEs, that there are problems faced in the Cibening Village environment, namely not yet knowing using of Cloud technology for digital promotion through MSME activities. We from Nusa Mandiri University Lecturers, assisted by a number of Students through Community Service activities, provide solutions to overcome the problems faced by PKK mothers and Cibening Village Staff to provide an introduction to Cloud technology as a form of promotion for MSME activities in Cibening Village. We do this with the aim of providing full assistance and support to PKK mothers and Village Staff through MSMEs in Cibening Village in utilizing Cloud technology as a means of promotion and product development through MSME activities in Cibening Village. The results of Community Service activities seen from the results of the pretest and posttest provided a significant change in scores obtained through a direct ranking method of five variables and ten indicators using a scale of six, resulting in a score with a total weight of 68.32 and good predicate. This provides a conclusion that the activities have been carried out are said to be successful.